An Exploration of the Effects of Forward-Looking Corporate Climate-Related Disclosure on Corporate Readiness, Information Credibility, and Utility - Bechtold, Sara (Université d'Ottawa | University of Ottawa, 2026)
Climate change creates profound uncertainties for firms, investors, and regulators, raising urgent questions about how organizations anticipate, plan for, and disclose their transition pathways. This dissertation investigates the role of forward-looking corporate climate-related disclosure tools in shaping organizational readiness and information credibility and utility for a transitioning world. Anchored in the research objective “How can forward-looking corporate climate-related disclosures provide credible, decision-useful information that supports organizational readiness and informs investment in a decarbonizing world?”, this dissertation is comprised of three interconnected papers. Paper 1, published in Canadian Public Policy (Bechtold et al. 2025), synthesizes 28 recognized, relevant, global disclosure guidelines to develop a conceptual framework of forward-looking credibility, and applies it to early-mover Canadian financial institutions. The findings highlight strong alignment with indicators of ambition, moderate alignment in specificity, resilience, and decision-usefulness, and low alignment with resource allocation and comparability. Paper 2 adapts this framework as an illustrative application to Canada’s oil and gas sector, deepening the analysis by situating firm behavior within a typology of incumbent actor strategies. It finds that firms initially characterized as positive deviants largely exhibit patterns of reluctant incrementalism when assessed against forward-looking credibility and implementation criteria, with only limited and selective instances of deviance. This duality illustrates both the constraints of path dependence and the potential of deviant leadership under more enabling policy conditions, and our findings suggest a progressive incrementalism policy pathway based on disclosure-derived proxies of strategic orientation and capacity. Paper 3 pressure-tests the framework through semi-structured interviews with Paper 1’s early-mover cases within Canada’s former Sustainable Finance Action Council, treated as investment-relevant actors. It explores how decision-makers interpret, prioritize, operationalize, or resist forward-looking disclosure elements, offering an investor-centered lens on disclosure credibility and utility. Our findings highlight a strong emphasis on market-based signals of credibility and competitiveness while underscoring the importance of mandates and regulatory certainty as enabling conditions for meaningful, decision-useful disclosure. Collectively, the findings support a novel hypothesis: that absent strong enabling conditions including robust mandates, forward-looking elements of climate-related disclosure are unlikely to generate decision-useful information at scale, even where it may support internal strategic awareness and process-based resilience within individual firms. While continued voluntary engagement with forward-looking tools can strengthen organizational resilience, strategic capacity, and alignment with emerging global norms, the evidence points toward a hybrid, progressively phased mandate attuned to short-, medium-, and long-term transition needs. This dissertation contributes to sustainability transitions theory, institutional theory, and scholarship on disclosure credibility and decision-usefulness. It also provides practical insights for policymakers, highlighting the importance of hybrid regulatory approaches that: (a) balance baseline mandates with incentives for beyond-compliance leadership; (b) overlay global best-practices with customized, context-sensitive policies; and (c) strengthen disclosure practices to improve credibility and utility of forward-looking disclosures within the sectoral and jurisdictional realities of Canada.
Keywords: climate disclosure; forward-looking; transition plans; sustainable finance; Canada; disclosure credibility; disclosure decision-usefulness; oil and gas incumbents; decarbonization; net-zero transition